An MC-SS Platform for Short-Range Communications in the Personal Network Context. (26th December 2007) - Noguet, Dominique; Laugeois, Marc; Popon, Xavier; Balamuralidhar, B.; Lobeira, Manuel; Sortur, Narasimha; Dasalukunte, Deepak; Dehos, Cedric; Bakirtzoglou, Zeta
Abstract : Wireless personal area networks (WPANs) have gained interest in the last few years, and several air interfaces have been proposed to cover WPAN applications. A multicarrier spread spectrum (MC-SS) air interface specified to achieve 130 Mbps in typical WPAN channels is presented in this paper. It operates in the 5.2 GHz ISM band and achieves a spectral efficiency of 3.25 b · s − 1 · Hz − 1 . Besides the robustness of the MC-SS approach, this air interface yields to reasonable implementation complexity. This paper focuses on the hardware design and prototype of this MC-SS air interface. The prototype includes RF, baseband, and IEEE802.15.3 compliant medium access control (MAC) features. Implementation aspects are carefully analyzed for each part of the prototype, and key hardware design issues and solutions are presented. Hardware complexity and implementation loss are compared to theoretical expectations, as well as flexibility is discussed. Measurement results are provided for a real condition of operations.